Tendencje rozwoju stosunków ekonomicznych Unii Europejskiej z Federacją Rosyjską i Chińską Republiką Ludową w warunkach globalizacji - PUŚLECKI, ZDZISŁAW W. (Rocznik Integracji Europejskiej, 2012)
The main aim of the article was the presentation of the tendencies of economic relations development of the European Union with the Russian Federation and the People’s Republic of China in the conditions of globalisation. The success of the Russian political leaders in their bilateral relations with the European Union show how important, in the mutual is approaching, are the rules and effectiveness of the international system built up in the past sixty years. An objective interest of the transatlantic community is therefore to the west, for safe and prosperous Russia, was idealistic and at the same time realistic. At the same time as it is also important, that Russia and not Africa whether the Middle East, is for Europe force, with the strategic nature. In the long term, to the european economy effectively and permanently follow in globalisation processes and that term was competitive with, Russia and China must first become innovative economy. In terms of prospective it should be emphasised that the best hope for the peaceful development of the international cooperation offers the most important actors contemporary on the world stage.